Father involvement during early childhood: A systematic review of the literature - Diniz, E. (2021)
During recent years, fathers’ involvement has been addressed as a key source of family well-being and positive child development. However, the pathways to father involvement and its consequences for child development are varied, influenced by social, cultural, and ecological variables, and lack a systematic integration. This paper aims to bridge this gap by offering a systematic review of studies examining the psychosocial processes of father involvement during early childhood over the last 10 years. A database search was performed using a combination of relevant keywords, leading to identification of 3,655 articles, with 109 manuscripts assessed for eligibility, and finally 59 included. Most of the studies examine determinants of father involvement, with an emerging number of studies relying on the father’s assessment and longitudinal designs. Nevertheless, the focus on white middle-class families is dominant, leaving unexplored father involvement in other cultures and contexts. The findings are analyzed aiming to open new avenues for future research.